FINANCIAL SYSTEM AND ECONOMIC GROWTH OF EMERGING MARKET COUNTRIES IN ASEAN - Ika Wahyu Cahyani; Regina Niken Wilantari; Endah Kurnia Lestari (UPT Penerbitan Universitas Jember)
Financial system is one of key factor to economic sustainability. The importance of the functioning financial sector is used for economic development and transaction to achieve the desired growth rate. This research is aimed to explain the effect of financial system toward the economic growth in emerging market countries in ASEAN, including: Indonesia, Malaysia, Philippiness and Thailand. The method used in this research is panel data regression analysis. The estimation results showing that financial system represented as the independent variables, consist of credit domestic to sector private (CDR), gross fixed capital formation (GFCF), and inflation (INF), simultaneously affecting GDP in significant way at probability error level (α=5%). In other hand, in partial test, all independent variables effect GDP significantly at probability error level (α=5%).